(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Introduction: anxiety problems are one of the most frequent emotional disorders in the general population and are mostly associated with other mental and physical health problems. The presence of this comorbidity contributes to greater generalized anxiety symptoms and complicates the medical or psychological treatment that the user may receive, making it necessary to identify probable cases using screening instruments for early intervention. Objective: to analyze the sources of evidence of the validity of the Generalized Anxiety Disorder-2 (GAD-2) in Peruvian adults from the general population. Material and method: instrumental research design and quantitative approach. 405 Peruvian adults residing in Lima during the first two weeks of April 2021 participated, selected through snowball sampling and inclusion criteria. Internal consistency and evidence based in relation to other variables were evaluated. Results: the reliability of the instrument by means of the Angoff-Feldt coefficient (rAF = .82) and the omega coefficient (ω = .81) were acceptable. In addition, the GAD-2 presents adequate evidence based in relation on other variables such as depression (r = .66; p = .001) and suicidal ideation (r = .58; p = .001), both statistically significant and size strong effect. Conclusions: The results of the study provide adequate sources of evidence for the validity of the GAD-2 and strengthen its use as a reliable screening instrument to evaluate anxiety in Peruvian adults of the general population, supporting the inferences and interpretations made from its scores.